THE EFFECT OF INFLATION ON ENTREPRENEURIAL DEVELOPMENT IN ANAMBRA STATE, NIGERIA - Peter Izuchukwu, Udeachu (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2023)
Entrepreneurship has become a widespread feature of the business environment throughout the years. It may favor national economies and is often regarded as one of the critical engines of economic growth and employment creation. Understanding the potential reasons for diversity in entrepreneurial development is thus critical for assisting the government and policymakers in adopting acceptable policies to support the creation and development of new businesses. In recent years, Nigeria's volatile economic reality, characterized by financial crises, has impacted entrepreneurship development. Thus, this paper investigated the effect of inflation on entrepreneurial development among youths in Anambra State, Nigeria. A convenience sample of three hundred and twenty-two undergraduates pooled from five tertiary institutions in the southeast participated in the study. The study result indicates that the assumption that the inflation would significantly and positively predict entrepreneurial development in Anambra State was confirmed at ? = .169, p< .05. Thus, the R2 indicated that the increasing inflation in the country contributes about 23.8% variation in entrepreneurial development in Anambra State, Nigeria. The study has implications for the development of entrepreneurship in Nigeria.